Methods for measuring quality of libraries - Bavakutty, M. (Ess Ess Publications, 2005)
Contents of material: Introduction. Marketing of library and information products and service. Quality concepts in libraries. Total quality management. Quality standards and libraries. Service quality. Library evaluation and performance measurement. Methods for collection of data. Methods for analysis of data. SERVQUAL, ascale for measuring service quality. LibQUAL, an instrument for measuring library quality. Library quality; a review. Quality of libraries; case studies